NORTH NUROTA STONE AGE OF THE MOUNTAIN RANGE PRELIMINARY STUDIES ON ARCHAEOLOGY - L. Ungalov (Journal Park Publishing, 2024)
One of the regions where the study of the Stone Age monuments of Central Asia has entered a new stage is the Nurota mountain ranges. This article provides information on the natural-geographical features of the mountain range, the studies on the stone age in the southern and northern ridges of the Nurota mountain range, and the new monuments and finds recorded in the period after 2018. The newly recorded monuments and finds are mainly recorded from the southern part of the northern Nurota mountain range, from the territories of the present Koshrabot district. In the article, together with the materials of the finds, the preliminary results of Zardolisoi-1 studies, which are recognized by researchers as a monument, are noted.
Keywords: Nurota mountain range, Poshshot, Uchtut, Paleolithic, Neolithic, Oboy, Minishkor, Pangat, Zardolisoi, nucleus, plate.